Distribution and susceptibility assessment of geological hazards in Zemuhe fault zone (Puge section) - Guanghui LI; Yongbo TIE; Yongjian BAI; Xiaohui XIONG (Zhongguo dizhi zaihai yu fangzhi xuebao, 2022)
Taking Zemuhe fault zone (Puge section) as the study area, the control effect and development law of geological disasters in the study area are analyzed; Seven evaluation factors such as elevation, aspect and slope from fault are selected to construct the evaluation index system. The weighted information model coupled with deterministic coefficient model and information model is used to evaluate the susceptibility of geological disasters through ArcGIS. The results show that the development of geological hazards in the study area has fault distance effect, elevation and slope micro geomorphic effect and stratigraphic effect;The areas of extremely high, high, medium and low prone areas are 46.75 km2, 123.78 km2, 215.73 km2 and 285.34 km2 respectively, accounting for 6.96%, 18.43%, 32.12% and 42.49% respectively. The research results have important practical significance for guiding the land spatial planning and geological disaster prevention in Zemuhe fault zone and similar regions.